1997
DOI: 10.2307/3579441
|View full text |Cite
|
Sign up to set email alerts
|

Sialyl Lewis X Mimetics Attenuate E-Selectin-Mediated Adhesion of Leukocytes to Irradiated Human Endothelial Cells

Abstract: Ionizing radiation causes histological changes in normal tissues that resemble those resulting from the inflammatory response. Inflammation is a multistep process requiring expression of adhesion molecules on the surface of endothelial cells which results in leukocyte extravasation. E-selectin is an adhesion molecule that mediates leukocyte "rolling" on the endothelium and is required for the inflammatory response. We quantified E-selectin expression and selectin-dependent adhesion of leukocytes to human endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 31 publications
3
37
0
Order By: Relevance
“…The effects of low-dose irradiation on them should be examined, to investigate the mechanisms of augmented immune responses by low-dose irradiation. Furthermore, expression of IL-2 receptors, Eselectin, and intercellular adhesion molecule-1 has been reported to be induced by low-dose irradiation [24][25][26][27]. These effects might also be involved in the augmentation of immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of low-dose irradiation on them should be examined, to investigate the mechanisms of augmented immune responses by low-dose irradiation. Furthermore, expression of IL-2 receptors, Eselectin, and intercellular adhesion molecule-1 has been reported to be induced by low-dose irradiation [24][25][26][27]. These effects might also be involved in the augmentation of immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…8 Recent experimental evidence suggests that radiation-induced expression of the membrane glycoproteins E-selectin and intercellular adhesion molecule 1 (ICAM-1) on endothelial cells is involved in the mechanisms mediating increased leukocyte-endothelial cell interactions after irradiation. 9,10 Platelet endothelial cell adhesion molecule 1 (PECAM-1/CD31) is a 130-kDa membrane glycoprotein belonging to the immunoglobulin supergene family and is constitutively expressed on the surface of endothelial cells, platelets and circulating leukocytes. Mounting evidence implicates its involvement in a number of cell adhesion processes that take place in the vasculature, such as leukocyte adhesion and transmigration, [11][12][13][14][15][16][17] the adherence of platelets to the vascular wall at sites of endothelial cell damage, 18 and endothelial cell-cell adherence 19 and migration, a process required for neovascularization that is essential for tissue growth and repair.…”
mentioning
confidence: 99%
“…Recent studies have shown that ICAM-1 expression is induced by ionizing radiation (9,10). Radiation-mediated ICAM-1 expression is required for leukocyte adhesion to irradiated endothelial cells in culture (10).…”
mentioning
confidence: 99%
“…Radiation-mediated ICAM-1 expression is required for leukocyte adhesion to irradiated endothelial cells in culture (10). Ionizing radiation has long been recognized to induce an inflammation-like response within irradiated tissues (11)(12)(13)(14).…”
mentioning
confidence: 99%